Creación de una línea de productos de pastelería en base a la jícama - Rodríguez Iza, Jéssica Mireya (2018)
The present Project is intended to create a line of pastry products based on one central ingredient: the jícama, “Smallantus Sonchifolius”, a tuberous root grown mostly in the highlands of Andean countries, which versatility makes it ideal for its application in the confectionary field. Its advantages will be presented in an additional handbook. The theoretical framework will be supported by the analytic-synthetic method which consists of an extensive gathering of information about the origin of the plant, as well as, about the evolution of pastry and bakery and the most common recipes with jícama in Ecuador. It is important to notice that all the mentioned content will be sustained by academic sources and that it will be an essential component into the investigation process. In addition, an analysis of the current situation of the suppliers of the tuber in the surrounding areas of the capital will be carried out in order to collect data about the annual production of the plant. The qualitative method will be used for interviewing the local producers. The experimentation stage will be focused on the inductive-deductive method and the preparation of four different delicacies with jicama as the main ingredient: “alfajores” with jicama syrup and sweet spices, jicama pie with tropical pastry cream, jicama cheesecake with a sauce of Andean red fruits on top and chocolate cake with jicama aroma. Satisfying results were obtained and then the validation took place with the help and support of a group of educators whose expertise was really valuable throughout the stage. Finally, it was important to develop a handbook for the line of products based on the synthetic method of modelling. It will contain standard recipes and will include the necessary regulations for the product in the future.